The Effect of Fake Local Branding and Hard Selling Strategies on Product Interest in Consumer Purchase Decisions for SKINTIFIC Cosmetic Products in Semarang City - Rahma Faiza Zakiyah; Marno Nugroho (MANAZHIM, 2026)
The increasing prevalence of Chinese cosmetic products in the Indonesian market, particularly the Skintific brand, has intensified scholarly attention to marketing strategies such as fake local branding and hard selling. However, limited studies have examined how these strategies influence product interest and consumer purchasing decisions among Indonesian consumers. This study aims to analyze the effect of fake local branding and hard-selling strategies on product interest and purchasing decisions for Skintific cosmetic products in Semarang, Indonesia. A quantitative survey design was employed, involving 100 respondents selected through purposive sampling based on the criterion of having tried or purchased Skintific products. Data were collected through online questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings indicate that fake local branding has a positive and significant effect on both product interest and purchasing decisions. Hard selling also positively and significantly influences product interest and purchasing decisions, while product interest plays an important role in shaping purchasing decisions and serves as an intervening variable linking marketing strategies to consumer buying behavior. These findings support the view that marketing strategies based on perceived local identity and persuasive sales techniques can shape consumer attitudes and purchasing actions in the cosmetics sector. The study concludes that the combination of fake local branding and hard-selling strategies effectively increases consumer interest and purchasing decisions toward Skintific products in the Indonesian cosmetics market. This study contributes to marketing and consumer behavior literature by extending understanding of branding and promotional strategies in the cosmetics industry. Practically, the findings provide insights for cosmetic companies in designing responsive marketing strategies aligned with local consumer preferences and digital market dynamics, while future research may examine additional factors such as brand trust, influencer credibility, and consumer ethnocentrism.